Gold nanoparticle should understand protein corona for being a clinical nanomaterial - Charbgoo, Fahimeh (2020)
Gold nanoparticles (AuNPs) have attracted great attention in biomedical fields due to their unique properties. However, there are few reports on clinical trial of these nanoparticles. In vivo, AuNPs face complex biological fluids containing abundant proteins, which challenge the prediction of their fate that is known as "bio-identity". These proteins attach onto the AuNPs surface forming protein corona that makes the first step of nano-bio interface and dictates the subsequent AuNPs fate. Protein corona formation even stealth active targeting effect of AuNPs. Manipulating the protein corona identity based on the researcher goal is the way to employ corona to achieve maximum effect in therapy or other applications. In this review, we provide details on the biological identity of AuNPs under various environmental- and/or physiological conditions. We also highlight how the particular corona can direct the biodistribution of AuNPs. We further discuss the strategies available for controlling or reducing corona formation on AuNPs surface and achieving desired effects using AuNPs in vivo by engineering protein corona on their surface.